Analysis of Full Day School Procurement as a Response to Social Change: A Sociological Perspective - Rohib Adrianto Sangia; Sardjana Orba Manullang; Imanuddin Hasbi; Irfan Nurdiansyah (HK-Publishing, 2022)
AbstractFull day schools are not the latest issue. America has long recognized and applied it in the world of schooling. This issue heated up in Indonesia as a logical consequence of two things; on the one hand the more uncomfortable the social environment for child development, while on the other hand the parents rarely accompany the children at home because they work all day long. Then, is there still a comfortable environment for our children? This paper examines FDS from the perspective of the sociology of education. That school as a learning organization has turned out to be the best institution in fortifying children from the negative effects of the increasingly unfriendly social environment.Keywords: Full Day School, Sociology of Education. AbstrakSekolah sehari penuh bukanlah isu terbaru. Amerika sudah lama mengenal dan menerapkannya dalam dunia persekolahan. Isu ini memanas di Indonesia sebagai konsekuensi logis dari dua hal; di satu sisi lingkungan sosial semakin tidak nyaman bagi perkembangan anak, sedangkan di sisi lain orang tua jarang menemani anak di rumah karena seharian bekerja. Lalu, apakah masih ada lingkungan yang nyaman untuk anak kita? Makalah ini mengkaji FDS dari perspektif sosiologi pendidikan. Bahwa sekolah sebagai organisasi pembelajaran ternyata menjadi lembaga terbaik dalam membentengi anak dari dampak negatif lingkungan sosial yang semakin tidak bersahabat.Kata kunci: Sekolah Sehari Penuh, Sosiologi Pendidikan.